Dantrolene Prevents the Lymphostasis Caused by Doxorubicin in the Rat Mesenteric Circulation - Van, Serena; Pal, Soumiya; Garner, Brittney R.; Steed, Kate; Sridharan, Vijayalakshmi; Mu, Shengyu; Rusch, Nancy J.; Stolarz, Amanda J. (Frontiers in Pharmacology, 2021)
Background and Purpose: Doxorubicin (DOX) is a risk factor for arm lymphedema in breast cancer patients. We reported that DOX opens ryanodine receptors (RYRs) to enact ’calcium leak’, which disrupts the rhythmic contractions of lymph vessels (LVs) to attenuate lymph flow. Here, we evaluated whether dantrolene, a clinically available RYR1 subtype antagonist, prevents the detrimental effects of DOX on lymphatic function. Experimental Approach: Isolated rat mesenteric LVs were cannulated, pressurized (4-5 mm Hg) and equilibrated in physiological salt solution and Fura-2AM. Video microscopy recorded changes in diameter and Fura-2AM fluorescence tracked cytosolic free calcium ([Ca2+i]). High-speed in vivo microscopy assessed mesenteric lymph flow in anesthetized rats. Flow cytometry evaluated RYR1 expression in freshly isolated mesenteric lymphatic muscle cells (LMCs). Key Results: DOX (10 µmol/L) increased resting [Ca2+i] by 17.5% ± 3.7% in isolated LVs (n=11). The rise in [Ca2+i] was prevented by dantrolene (3 µmol/L; n=10). A single rapid infusion of DOX (10 mg/kg i.v.) reduced positive volumetric lymph flow to 29.7% ± 10.8% (n=7) of baseline in mesenteric LVs in vivo. In contrast, flow in LVs superfused with dantrolene (10 µmol/L) only decreased to 76.3% ± 14.0% (n=7) of baseline in response to DOX infusion. Subsequently, expression of the RYR1 subtype protein as the presumed dantrolene binding site was confirm in isolated mesenteric LMCs by flow cytometry. Conclusion and Implications: We conclude that dantrolene attenuates the acute impairment of lymph flow by DOX and suggest that its prophylactic use in patients subjected to DOX chemotherapy may lower lymphedema risk.